Pinpointing the role of Aeromonas salmonicida in the development of skin ulcerations in common dab ( Limanda limanda ) - Maaike Vercauteren; Evelien De Swaef; Annelies Maria Declercq; Johan Aerts; Bart Ampe; Snorre Gulla; Freddy Haesebrouck; Lisa Devriese; Annemie Decostere; Koen Chiers (Journal of Fish Diseases, 2020)
Aeromonas salmonicida was isolated from ulcerations in common dab ( Limanda limanda ). An experiment was performed to pinpoint its role in ulceration development, considering the importance of the skin barrier and the pigmented and non‐pigmented sides. The skin of dab was treated in three zones, one where scales and epidermis were removed, one where mucus was discarded and one non‐treated zone. Fish were tagged to allow individual identification and challenged with A. salmonicida . Mortality and severity of the developing lesions were recorded for 21 days post‐inoculation. Starting 12 days post‐inoculation, mortality occurred gradually in challenged fish; however, no direct cause could be established. Both control fish and challenged fish developed ulcerations containing A. salmonicida. S equencing of vap A gene revealed that isolates retrieved from both groups were distinct, suggesting the presence of A. salmonicida prior to the trial. Most ulcerations developed in zones where skin was removed, suggesting that abrasion might be a predisposing factor in ulceration development. Ulcerations were also observed at the insertion site of the tag, where exposed muscle tissue might have favoured the development of ulcerations . In conclusion, A. salmonicida seems to be involved in the development of skin ulcerations in dab, although the exact pathogenesis needs to be elucidated.